La Historia de Sta. Ana de Sapa linked streetscapes development highlighting the traditional imprint of Sta. Ana heritage district - Biascan, Amabelle Faye L. (College of Architecture, University of the Philippines Diliman, 2019)
Sta. Ana Heritage Zone was declared as a histo-cultural overlay zone on 2014 because of it having various historical landmarks and heritage houses. Threatened by the continuous development and construction of high-rise buildings, the community are fighting for the preservation of the historical landmarks and buildings of Sta. Ana. My study aims to develop linked streetscapes along the district that help address the issue and narrate and highlights the town's heritage significance. The development will involve a walkable pedestrian tourism and conservation system that will include the application of a historical narrative and intangible qualities of the district into the development of the streetscapes and open spaces. This will be incorporated into tangible features of streetscape such as the materials, features and planting design. It will also establish the linkage and connectedness of various open spaces and key areas along the town to promote the walkable pedestrian tourism system.